2015
DOI: 10.1111/1462-2920.12728
|View full text |Cite
|
Sign up to set email alerts
|

Response of intertidal benthic microalgal biofilms to a coupled light–temperature stress: evidence for latitudinal adaptation along the Atlantic coast of Southern Europe

Abstract: Although estuarine microphytobenthos (MPB) is frequently exposed to excessive light and temperature conditions, little is known on their interactive effects on MPB primary productivity. Laboratory and in situ experiments were combined to investigate the short-term joint effects of high light (HL) and high temperature (37 °C versus 27 °C) on the operating efficiency of photoprotective processes [vertical migration versus non-photochemical quenching (NPQ)] exhibited by natural benthic diatom communities from two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 74 publications
3
78
1
Order By: Relevance
“…also showed sensitivity to temperature change (Sobrino and Neale, 2007). The repair rates (r) and the ratio of r to k further demonstrated that the planktonic species had a relatively lower optimal temperature in response to UVR, with the highest r : k and lowest UV inhibition at 25 • C. In contrast, in the benthic species r and r : k increased steadily and reached relatively stable values at the highest temperature, and this coincided with lower UV inhibition, implying that although acclimated in laboratory conditions for weeks, this species still had an active mechanism to respond to high temperature and UVR, as might occur in its natural niche environment (Laviale et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…also showed sensitivity to temperature change (Sobrino and Neale, 2007). The repair rates (r) and the ratio of r to k further demonstrated that the planktonic species had a relatively lower optimal temperature in response to UVR, with the highest r : k and lowest UV inhibition at 25 • C. In contrast, in the benthic species r and r : k increased steadily and reached relatively stable values at the highest temperature, and this coincided with lower UV inhibition, implying that although acclimated in laboratory conditions for weeks, this species still had an active mechanism to respond to high temperature and UVR, as might occur in its natural niche environment (Laviale et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…These findings imply that temperature is a key factor that mediates the response of diatoms to UVR, while different species have developed distinct mechanisms in response to their particular niche environments (Laviale et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This striking contrast of physiological traits in coastal and oceanic diatoms suggests that the ability to cope with fluctuating carbonate chemistry may play a role in influencing the geographic distributions of species under OA conditions. It is possible that this ability, together with the abilities to cope with nutrient (Irwin et al, 2006), light (Lavaud et al, 2007;Lavaud and Lepetit, 2013;Laviale et al, 2015), and predation pressure (Irigoien et al, 2005), will determine the spatial distribution patterns of species in the future oceans. However, phytoplankton are known to exhibit species-specific response to environmental factors (including OA, fluctuating carbonate chemistry, etc.…”
Section: Discussionmentioning
confidence: 99%